PL.02 Inflammatory Signalling in Fetal Membranes: The Transcriptome of Chorioamnionitis. (26th April 2013) - Waring, GJ; Robson, SC; Bulmer, JN; Tyson-Capper, AJ
Abstract : Introduction: Inflammation(with or without infection) has a firm causal link and defined molecular pathophysiology for preterm birth (PTB) with histological chorioamnionitis (CA) being a sensitive and specific marker. The innate immune system uses Toll-like receptors (TLRs) to recognise different microorganisms. This study profiles TLR signalling in fetal membranes from PTBs with and without CA. Methods: Fetal membrane explants were collected from 3 groups of women; term spontaneous labour without CA (TSL-CA) (n = 10), PTB < 34 weeks without CA (PTB-CA) (n = 8), PTB < 34 weeks with CA (PTB+CA) (n = 13). CA was determined by Redline criteria (maternal inflammatory response ≥ stage 2). Membranes were separated into amnion and chorion and RNA extracted. Profiling arrays were used to determine the expression profile of 84 genes associated with TLR signalling. Individual genes shown to be significantly up or down regulated (P < 0.1; fold change >2) were selected for validation by qPCR. Results: In the amnion 11 genes were differentially expressed (6 between PTB+CA and TSL-CA and 5 between PTB+CA and PTB-CA. In the chorion 16 genes were differentially expressed (6 between PTB+CA and TSL-CA and 10 between PTB+CA and PTB-CA). Validation confirmed increased expression of TLR1 in amnion (p = 0.03) and chorion (p = 0.001) and increased expression of TLR2 in amnion (p = 0.04) and chorion (p = 0.0005) in PTB+CA compared with TSL-CA (Figure 1 ). Conclusion: These data show a correlation between the presence of CA and up-regulation of TLR1 and TLR2, but not TLR6. These novel findings have implications for both the identity of the microorganisms and the mechanism(s) contributing to inflammation associated with PTB with CA.